Pelaksanaan Pekerjaan Struktur Pondasi Dan Kolom Neut Pada Pembangunan Gedung Assesment Kejiwaan Di Rumah Singgah - Misnawati, *; Rahimah, Helda Aulia; Zakiah, Raudatul (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
The construction of public service buildings requires the implementation of proper structural work to ensure the strength, stability, and safety of the building. This study aims to evaluate the implementation of the work of the foundation structure and neut columns in the Psychiatric Assessment Building Construction Project at the Banjarmasin City Shelter. The study focuses on the stages of implementation, construction methods, use of materials, concrete quality control, and field conditions that have the potential to affect the quality and smoothness of structural work. The research method used is a descriptive method through field observation and document studies. Data were obtained from direct observation of the implementation of structural work and evaluation of the suitability of implementation in the field against the plan drawings, technical specifications, and applicable construction standards. The foundation work includes piling the galam poles, excavating the soil, installing sand urug, making a work floor, installing formwork and reinforcement, and casting K-300 quality ready mix concrete. The work of the neut column includes determination of axle points, reinforcement assembly, installation of formwork, and casting of K-250 quality concrete. The results of the study showed that the slump value and compressive strength of concrete generally met the quality of the plan. However, field conditions such as standing water and casting during rain have the potential to affect the quality of work and cause adjustments to implementation times. In general, the implementation of structural work has been in accordance with the stages and work methods based on applicable construction standards, but more optimal control of field conditions and supervision is needed to ensure the quality of the structure and the smooth running of the project.